ANALYSIS OF FINANCIAL LITERACY LEVELS ON CONSUMPTIVE BEHAVIOR AND INVESTMENT INTERESTS OF STUDENTS ECONOMIC EDUCATION STUDY PROGRAM FKIP ULM - Rizky, Maulana; Azzahra, Maulida Ilma; Suratno, Suratno (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
This study aims to: determine and analyze the level of financial literacy of students and determine the effect of financial literacy on consumptive behavior and investment interest of students of the Economic Education study program FKIP ULM. This research method is descriptive quantitative, the sample in the research using proportionate stratified random sampling consists of 183 active students of the Economic Education study program FKIP ULM. Data collection techniques using a questionnaire. The results of the descriptive analysis of the level of financial literacy show that the level is in the medium category with a percentage of 75.6%. On moderate consumptive behavior with a percentage of 73.2%, and moderate investment interest with a percentage of 75.8%. The results of the hypothesis test say that the effect between financial literacy and consumptive behavior is significant with a T-Statistic of 5.020 (> 1.96) with an original sample estimate value of 0.376 or 0.000 on P Values, and between financial literacy and significant investment interest with T-Statistics 5.615 (> 1.96) and the original sample estimated value is 0.494 or 0.000 in P Values. The magnitude of the effect is seen from R square, namely financial literacy has an effect of 14.2% and 24.4%, which means that it has a small effect on consumptive behavior and investment interest, while the rest is explained by other variables not included in this study.